2020
DOI: 10.3389/fneur.2020.00721
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modifiers of Duchenne Muscular Dystrophy in Chinese Patients

Abstract: Background: Duchenne muscular dystrophy (DMD) is a fatal, X-linked recessive muscle disorder characterized by heterogeneous progression and severity. We aimed to study the effects of single nucleotide polymorphisms (SNPs) in SPP1 and LTBP4 on DMD progression in Chinese patients. Methods: We genotyped LTBP4 haplotypes and the SPP1 promoter SNPs rs28357094, rs11730582, and rs17524488 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 39 publications
0
27
1
Order By: Relevance
“…Of the 259 studies identified, 8 met the inclusion criteria and were included in the systematic review [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and 4 were included in the meta-analysis ( Table 1 and Figure 1 ) [ 20 , 21 , 22 , 24 ]. Four studies were excluded for various reasons ( Supplementary Table S1 ) [ 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 259 studies identified, 8 met the inclusion criteria and were included in the systematic review [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], and 4 were included in the meta-analysis ( Table 1 and Figure 1 ) [ 20 , 21 , 22 , 24 ]. Four studies were excluded for various reasons ( Supplementary Table S1 ) [ 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, regarding SPP1 rs11730582 and rs17524488, only rs11730582 genotype C showed a protective association, with an HR = 0.63 (95% CI: 0.45, 0.89) [21]. no significant effect [20,21]. SPP1 rs28357094 showed no association [20,24].…”
Section: Loss Of Ambulation-cox Regression Analysesmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, the design of this panel allows us to add on additional probes covering other modifier genes like LTBP4, which is believed to accelerate muscle regeneration and alleviate muscle fibrosis by reducing TGF-β signalling. Phosphatidylinositol transfer protein α (PITPNA) and Jagged1 that ameliorate the pathology of DMD, Anxa6 that encodes annexin A6, a calcium-binding protein that regulates the injury pathway, and sarcolemmal resealing, decreased expression of TCTEX1D1 could be deleterious for the cardiac phenotype in patients with DMD and Osteopontin; encoded by the SPP1 gene which plays a role in DMD pathology modulating muscle inflammation and regeneration (Chen et al, 2020;Spitali et al, 2020;Vieira et al, 2015). We tested this panel on a set of 24 confirmed DMD patients from 22 families and the members from their matrilineage for up to four generations.…”
Section: Discussionmentioning
confidence: 99%